Immunohistochemical study of bone marrow angiogenesis in multiple myeloma and its correlation with clinicopathological factors - Buraid, Hasan A.; Jaafar, Abdulkareem M.; Naji, Rana Z. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: In recent years, bone marrow angiogenesis was reported to be involved in the pathogenesis and progression of certain hematological malignancies like multiple myeloma, leukemias, and lymphomas. Recent studies have suggested that bone marrow angiogenesis plays an important role in the pathogenesis and prognosis of multiple myeloma. Objectives: at the present study, bone marrow angiogenesis in multiple myeloma was examined using immunohistochemical staining for CD34, and correlated with various pathological and clinical parameters. Patients and methods: This is a retrospective study; where by archival paraffin-embedded tissue blocks along with the clinical and hematological records of fifty-two patients with multiple myeloma and twenty controls were obtained from the Department of Hematology of the Medical City Teaching Laboratories in the period from January 2010 to January 2013. Bone marrow angiogenesis was studied by immunohistochemical staining for CD34 to identify microvessels. Results: There was a significant association between higher angiogenesis grades and advanced clinical stage of the disease (p = 0.002), and higher plasma cell percent in the bone marrow (p = 0.03), and increasing immaturity of the plasma cell (p = 0.001), and diffuse pattern of bone marrow infiltration by plasma cells (p = 0.007). Conclusions: Patients with increased plasma cell burden, immature plasma cell morphology, and diffuse pattern of infiltration had a higher microvessel density.